An exploratory study of early letter-sound knowledge in a low socio-economic context in South Africa - O'Carroll, Shelley (Aosis publishing, 2011)
This paper explores one aspect of early literacy development in a low socio-economic context in South Africa. Assessments conducted with a sample of children from two disadvantaged communities in Cape Town indicated that in this context, almost half of the learners entering Grade One were unable to recognise any letters. A Grade R intervention conducted by volunteers showed that children from this context were able to learn letter-sounds in Grade R through a programme that focused on teaching letter-sounds in the context of building language skills, emergent writing and concepts about print. In order to strengthen the effectiveness of the intervention, the volunteer programme was supplemented by support for the Grade R teacher and teaching assistant. Follow-up assessments of one of the intervention groups at the end of Grade One revealed significant correlations between early Grade One letter knowledge and end of Grade One word reading and spelling skills. The findings of this exploratory study are in line with research that shows the importance of letter-sound knowledge in the earliest stages of learning to read. This raises concerns about the historical lack of emphasis in the Grade R curriculum on this aspect of early literacy development. Although the study has a narrow focus and conclusions cannot be drawn about other aspects of early literacy learning in this context, the results suggest an urgent need for quality Grade R teacher training programmes with a specific focus on emergent literacy.
Keywords: letter knowledge; word reading; early intervention; emergent literacy